2017
DOI: 10.1039/c7ra05020h
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose enzymatic saccharification and preparation of 5-hydroxymethylfurfural based on bamboo hydrolysis residue separation in ionic liquids

Abstract: Ionic liquid/ethanol was used in bamboo hydrolysis residue (BHR) to separate lignin and cellulose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Other bands, indicating the presence of both carboxylic acids and aldehydes, are those close to 1390 cm À1 and 1427 cm À1 , characteristics of the out of plane OH bending of dimeric acids and of CH bending of aldehydes, respectively. The relatively intense signals in the 1000-1400 cm À1 range can be attributed to the COC vibrations of the furan ring generally observed for the 5-HMF, 55 whose presence is also supported by weak signals at about 1600 cm À1 due to the C-C double bond stretching vibration.…”
Section: Ft-ir Characterization Of Bio-oilmentioning
confidence: 69%
“…Other bands, indicating the presence of both carboxylic acids and aldehydes, are those close to 1390 cm À1 and 1427 cm À1 , characteristics of the out of plane OH bending of dimeric acids and of CH bending of aldehydes, respectively. The relatively intense signals in the 1000-1400 cm À1 range can be attributed to the COC vibrations of the furan ring generally observed for the 5-HMF, 55 whose presence is also supported by weak signals at about 1600 cm À1 due to the C-C double bond stretching vibration.…”
Section: Ft-ir Characterization Of Bio-oilmentioning
confidence: 69%
“…The enzyme molecule adsorbs to the cellulose's surface forming an unstable enzyme-substrate unit with the substrate further converted into reducing sugars. The adsorption quantity could also reach a maximum value when the enzyme binding to the substrate reach a saturated value producing a relative high saccharification yield, but the adsorption extent could not be increased when the cellulose is exposed to higher enzyme concentrations beyond a certain value (Kassanov et al, 2017). The highest relative percentage saccharification of newspaper was calculated at 23% when 20 mg/mL of enzyme dosage was added used for saccharification of newspaper.…”
Section: Resultsmentioning
confidence: 98%
“…Studies have shown that washing the IL-activated biomass could dramatically improve hemicellulose conversion, since the hydrolytic enzymes are more sensitive to the presence of ionic liquids as well as to inhibitors such as humins that are generated during IL-activation. 33,34 The partial removal of hemicellulose and lignin during autohydrolysis and the structural changes undergone by cellulose during IL activation together resulted in higher carbohydrate conversion of the sequentially pretreated HP. Cellulose structure has been reported to have a significant impact on enzymatic saccharification kinetics, where cellulose II was more digestible than cellulose I.…”
Section: Comparison Of Saccharificationmentioning
confidence: 99%